WORKSHOP ECO-PRINT DALAM PEMBERDAYAAN MASYARAKAT KAWASAN WISATA HUTAN MERANTI - Nadia Almira Jordan; Sasferi Yendra (Jurnal Abdi Insani, 2023)
Environment-based tourism is a concept developed to manage natural tourism such as the Meranti Forest Tourism Area. The tourism potential, which is managed by the community is in the Meranti tree forest and attractions such as a camping ground. Even though it is a well-known tourist destination of Balikpapan, the location has not yet fulfilled the elements of a tourism component, for example, complementary elements and souvenirs. The area development plan is also not yet available, so the manager is not able to conduct a promotion to investors. Community service activities aim to develop the area through community empowerment according to tourism needs. In particular, the planned program aims to provide understanding and skills in making souvenirs to encourage community entrepreneurship. The target of the activity was residents around the location, Km 15 RT 27, Karang Joang Village, Balikpapan City. This activity uses counseling and simulation methods, with initial observations of the area's potential. The executor conducts outreach, followed by direct practice by the community and a questions and answers session. The activity results are the implementation of making and installing sign boards at the sites, increasing the knowledge and skills of residents in making souvenirs, and the availability of master plans. The first program produces signboards that are installed on tourist sites. The results of the second program are eco-print products made by women and the evaluation of activity testimonials. The third product is a regional master plan drawing album produced through discussion forums and design simulations using virtual reality. All results were obtained through the process of observing the study of natural and human resources in the area. Community empowerment is carried out to provide knowledge and to increase empowerment so that the community can play an active role as the subject of tourism area development.